Expatriates and Managing Global Mobility - Min Toh, Soo; DeNisi, Angelo (Taylor & Francis, 2023)
There has been several decades of research on why women are under-represented in the expatriate population, but it is only in the past few years that research has begun to focus on issues with members from other diverse groups and how they fit into the expatriate picture. This chapter's authors spotlight gender, age, race, religion and sexual orientation diversity. They point out, however, that MNCs can help alleviate some of these issues by fostering strong diversity climates within the firm, including diversity training programs, but clear evidence for the success of the various attempts to increase diversity is lacking. This chapter highlights how there is a special need for research which considers the intersection of these various dimensions of diversity, and how that can affect expatriate experience.